The life of D. H. Lawrence : a critical biography - Harrison, Andrew, 1973- (Chichester, Sussex : Wiley-Blackwell, 2016)
"Offers fresh insights into the life, work, and legacy of D.H. Lawrence, drawing on his writings and letters, as well as the latest scholarship and biographical sources"--
Machine generated contents note: Preface -- Literary Formation, 1885-1912. Early Voices, September 1885-October 1908 -- Literary London, October 1908-April 1910 -- 'A Small but Individual Name', April 1910-May 1912 -- UnEnglished, 1912-1914. 'Coming Out Wholesome and Myself', May 1912-May 1913 -- Forging a Career, June 1913-August 1914 -- The Bitterness of the War and its Aftermath, 1914-1919. 'The Real Fighting Line', August 1914-December 1915 -- Outlaw, December 1915-April 1918 -- 'Laid Up', May 1918-November 1919 -- Europe Again, 1919-1922 -- Italy and Sicily, November 1919-December 1920 -- End of the Line, January 1921-February 1922 -- New Worlds and Old Worlds, 1922-1925. Ceylon and Australia, February-August 1922 -- On to America, August 1922-November 1923 -- Broken Bonds, December 1923-July 1924 -- Writing for the Race, August 1924 -September 1925 -- Returning, 1925-1927. Understanding, September 1925-April 1926 -- Writing and Painting, April 1926-March 1927 -- 'Unfailing Courage', 1927-1930. Friendship and Isolation, March 1927 -May 1928 -- 'Dropping a Little Bomb in the World's Crinoline of Hypocrisy', May 1928-August 1929 -- 'Living on his Spirit', August 1929 -March 1930 -- Afterword.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Lawrence, D. H. -- 1885-1930.; Lawrence, D. H. -- 1885-1930.; 1900-1999; Authors, English -- 20th century -- Biography; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Authors, English; Biography; Electronic books